Pemberdayaan Masyarakat Desa Talunkidul melalui Pelatihan Budidaya Hidroponik Menuju Ketahanan Pangan - Mohammad Fatchulloh; Dyah Ayu Sri Hartanti; Ibrahim Ibrahim; Salsabila Nurzamzami; Adelia Eka Putri; Noermawati Putri; Muhammad Rizky Ikhwansyah (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
The development of modern agricultural technology requires rural communities to adapt in addressing the challenges of limited land and increasing food demand. One promising solution is hydroponic cultivation, an efficient method that enables households to produce high-quality crops in restricted spaces. This community engagement program was carried out in Talunkidul Village, Sumobito District, by involving members of the women’s PKK group as the primary partners. The main objective was to enhance community knowledge and skills in modern farming practices while fostering awareness of the importance of household food security. The program was implemented through educational, collaborative, and practical approaches, including seminars, interactive discussions, hands-on training in constructing simple hydroponic systems, and technical mentoring after training. The results demonstrated an improvement in participants’ understanding and practical skills in utilizing hydroponic technology, the establishment of a simple hydroponic installation as a learning model, and the emergence of community motivation to apply hydroponics at the household level. Beyond skill acquisition, the program also encouraged collective awareness of community-based food security. Therefore, this activity functioned not only as a transfer of knowledge but also as an empowerment effort that contributed to sustainable food independence in rural areas.